Intravenous immunoglobulin in drug and device refractory patients with the symptoms of gastroparesis—an open‐label study. Issue 3 (4th December 2017) - Ashat, M.; Lewis, A.; Liaquat, H.; Stocker, A.; McElmurray, L.; Vedanarayanan, V.; Soota, K.; Howell, T.; Kedar, A.; Obert, J.; Abell, T. L.
Abstract: Background: Gastroparesis is a complex clinical entity; many aspects of which remain unknown. Although most patients have idiopathic, diabetic, or postsurgical gastroparesis, many are thought to have measurable neuromuscular abnormalities. Immunotherapy has recently been utilized to treat suspected autoimmune gastrointestinal dysmotility. Methods: Fourteen patients with symptoms of gastroparesis (Gp) who were refractory to drug/device were selected from 443 Gp patients from 2013 to 2015 who were treated at the University of Louisville motility center. All patients underwent a structural and psychiatric evaluation along with detailed psychological and behavioral examination to rule out eating disorders. We performed detailed neuromuscular evaluation and all 14 patients received at least 12 weeks of intravenous immunoglobulin (400 mg/kg infusion weekly). Response was defined subjectively (symptomatic improvement) using standardized IDIOM score system. Key Results: All 14 patients had serological evidence and/or tissue evidence of immunological abnormality. Post‐IVIG therapy, there was a significant improvement in symptoms scores for nausea, vomiting, early satiety, and abdominal pain. Conclusions and Inferences: Although limited by the absence of placebo group, the data illustrate the role of autoimmunity and neuromuscular evaluation in patients with gastroparesis and support the utility of a diagnostic trial of immunotherapy in an effort to improve therapeutic outcomes for such patients. Abstract : Many patients with the symptoms of gastroparesis are refractory to all currently used therapies. We performed an open‐label study on 14 such patients with weekly intravenous immunoglobulin, usually for 12 weeks. Post‐IVIG, the patients as a group improved in nearly all symptoms of gastroparesis.